Tourism and Sustainable Development - Auroubindo Ganesh, A; Madhavi, Dr C (Journal of Contemporary Research in Management (JCRM), 2013)
Tourism is not only a pleasure trip to the visitors but also the largest and the fastest developing industry in the world today. It emerges as a creator of jobs across national and regional economies. WTTC I WEFA research show that Travel & Tourism generated, directly and indirectly, more than 11.7% of GDP and nearly 238 million jobs in the worldwide economy. These figures are forecasted to total 11.7% and 255 million respectively in 2010. Jobs generated by Travel & Tourism are spread across the economy - in retail, construction, manufacturing and telecommunications, as well as directly in Travel & Tourism companies. These jobs employ a large proportion of women, minorities and young people; are predominantly in small and medium sized companies; and offer good training and transferability. Tourism can also be one of the most effective drivers for the development of regional economies. These pattems apply to both developed and emerging economies. It acts as one of the socio - economic tools for sustainable developments of many nations. In addition, it wonderfully works to preseNe nature, culture and heritage of nations. If carefully managed, Tourism can be used to attain the goal of all states that is to eliminate poverty. Many types of Tourism such as Eco- Tourism, heritage Tourism can lift the income of the local people living inÂ  and around forests, coastal villages by using their culture, heritage, natural environments etc.